ANALYSIS OF THE LANGUAGE STYLE OF SINEKDOKE PARS PRO TOTO AND TOTUM PRO PARTE IN KOMPAS NEWSPAPER - Siti arfina; Tri Yuliawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the form and function of the synecdoke language style in national newspaper news texts and explain its role in the construction of the meaning of journalistic discourse. The research uses a qualitative approach with a descriptive method. The research data is in the form of eleven excerpts of news texts published in the January-February 2026 period in national newspapers. Data was collected through documentation techniques and analyzed using content analysis techniques with stages of reduction, classification, interpretation, and conclusion drawn. The validity of the data was tested through diligence of observation and triangulation of stylistic theory and functional linguistics. The results of the study show that there are two main forms of synecdoke, namely pars pro toto and totum pro parte, with different distributions according to the characteristics of the news rubric. The pro toto form of pars is found in the use of part elements to represent the whole entity, especially in the rubrics of law, opinion, and humanities. Meanwhile, the form of totum pro parte is more dominant in the rubric of sports and technology through the mention of collective entities, such as the name of the country, to refer to a specific group. Functionally, both forms act as representational strategies that simplify reality, build dramatic effects, and strengthen the reader's collective identity and emotional closeness.These findings confirm that journalistic language is not completely neutral, but rather works through structured representation mechanisms. Synecdoke in news texts serves as a systematic stylistic device in building the meaning and perspective of discourse. This research contributes to the development of media stylistic studies and can be a reference in learning the analysis of language styles and mass media discourse.